A new promising candidate to overcome drug resistant herpes simplex virus infections - Zinser, Elisabeth; Krawczyk, Adalbert; Mühl-Zürbes, Petra; Aufderhorst, Ulrich; Drassner, Christina; Stich, Lena; Zaja, Mirko; Strobl, Stefan; Steinkasserer, Alexander; Heilingloh, Christiane (Antiviral Research, 2018)
Infections with Herpes simplex viruses (HSV) belong to the most common human diseases worldwide, resulting in symptoms ranging from painful, but commonly self-limiting lesions of the orofacial or genital tract to severe infections of the eye or life-threatening generalized infections. Frequent HSV-reactivations at the eye may lead to the development of herpetic stromal keratitis, which is one of the major causes of infectious blindness in developed countries. The vast majority of life-threatening generalized infections occur in immunocompromised individuals, such as transplant recipients or patients suffering from advanced human immunodeficiency virus (HIV) infection with concurrent HSV-reactivation. Over the past decades, Acyclovir (ACV) became the golden standard for the treatment of HSV infections. However, long-term antiviral treatment, as it is required mainly in immunocompromised patients, led to the emergence of resistances towards ACV and other antivirals. Therefore, there is a clear need for the development of new potent antivirals which combine good oral bioavailability and tolerability with low side effects. In the current study we present SC93305 as a novel potent antiviral substance that proved to be highly effective not only against different HSV-1 and HSV-2 strains but also towards ACV- and multi-resistant HSV-1 and HSV-2 isolates. SC93305 shows comparable antiviral activity as reported for ACV and very importantly it does not interfere with the activation of specific immune cells. Here we report that SC93305 does not affect the biological function of dendritic cells (DC), the most potent antigen presenting cells of the immune system to induce antiviral immune responses, nor T cell stimulation or the release of inflammatory cytokines. Thus, SC93305 is a new and promising candidate for the treatment of HSV-1 and HSV-2 infections and in particular also for the inhibition of drug-resistant HSV-1/2 strains.
EVALuna2:34804

Antibody-based immunotherapy of aciclovir resistant ocular herpes simplex virus infections - Bauer, Dirk; Keller, Jessica; Alt, Mira; Schubert, Axel; Aufderhorst, Ulrich Wilhelm; Palapys, Vivien; Kasper, Maren; Heilingloh, Christiane; Dittmer, Ulf; Laffer, Bjoern; Eis-Huebinger, Anna Maria; Verjans, Georges M.; et al. (Virology, 2017)
The increasing incidence of aciclovir- (ACV) resistant strains in patients with ocular herpes simplex virus (HSV) infections is a major health problem in industrialized countries. In the present study, the humanized monoclonal antibody (mAb) hu2c targeting the HSV-1/2 glycoprotein B was examined for its efficacy towards ACV-resistant infections of the eye in the mouse model of acute retinal necrosis (ARN). BALB/c mice were infected by microinjection of an ACV-resistant clinical isolate into the anterior eye chamber to induce ARN and systemically treated with mAb hu2c at 24h prior (pre-exposure prophylaxis) or at 24, 40, and 56h after infection (post-exposure immunotherapy). Mock treated controls and ACV-treated mice showed pronounced retinal damage. Mice treated with mAb hu2c were almost completely protected from developing ARN. In conclusion, mAb hu2c may become a reliable therapeutic option for drug/ACV-resistant ocular HSV infections in humans in order to prevent blindness.
EVALuna2:36335

A Therapeutic Antiviral Antibody Inhibits the Anterograde Directed Neuron-to-Cell Spread of Herpes Simplex Virus and Protects against Ocular Disease - Bauer, Dirk; Alt, Mira; Dirks, Miriam; Buch, Anna; Heilingloh, Christiane; Dittmer, Ulf; Giebel, Bernd; Goergens, Andre; Palapys, Vivien; Kasper, Maren; Eis-Huebinger, Anna M.; Sodeik, Beate; et al. (Frontiers in Microbiology, 2017)
Herpes simplex virus (HSV) is a leading cause of blindness and viral encephalitis in the developed world. Upon reactivation from sensory neurons, HSV returns via axonal transport to peripheral tissues where it causes, e.g., severe, potentially blinding ocular diseases. In the present study we investigated whether the HSV-1/2 glycoprotein B-specific antibody mAb 2c or its humanized counterpart mAb hu2c can protect from ocular disease in a mouse model of HSV-1-induced acute retinal necrosis (ARN). In this model the viral spread from the initially infected to the contralateral eye resembles the routes taken in humans upon HSV reactivation. Systemic antibody treatment prior or early after infection effectively protected the mice from the development of ARN. These observations suggest that the antibody potently neutralized the infection and inhibited the viral transmission, since there was almost no virus detectable in the contralateral eyes and trigeminal ganglia of antibody treated mice. Besides of neutralizing free virus or limiting the infection via activating the complement or cellular effector functions, blocking of the anterograde directed neuron-to-cell spread of HSV represents a viable mode of action how mAb 2c protected the mice from ARN. We proved this hypothesis using a microfluidic chamber system. Neurons and epithelial cells were cultured in two separate compartments where the neurons sent axons via connecting microgrooves to the epithelial cells. Neurons were infected with a reporter HSV-1 strain expressing mCherry, and the co-culture was treated with neutralizing antibodies. In contrast to commercial polyclonal human HSV-neutralizing immunoglobulins, mAb 2c effectively blocked the anterograde directed neuron-to-cell transmission of the virus. Our data suggest that the humanized HSV-1/2-gB antibody protects mice from ocular disease by blocking the neuronal spread of HSV. Therefore, mAb hu2c may become a potent novel therapeutic option for severe ocular HSV infections.
EVALuna2:36336

Autophagic degradation of lamins facilitates the nuclear egress of herpes simplex virus type 1 - Turan, Aykut; Grosche, Linda; Krawczyk, Adalbert; Mühl-Zürbes, Petra; Drassner, Christina; Düthorn, Alexandra; Kummer, Mirko; Hasenberg, Mike; Voortmann, Sylvia; Jastrow, Holger; Dörrie, Jan; Schaft, Niels; et al. (The Journal of Cell Biology, 2019)
Dendritic cells (DCs) are crucial for the induction of potent antiviral immune responses. In contrast to immature DCs (iDCs), mature DCs (mDCs) are not permissive for infection with herpes simplex virus type 1 (HSV-1). Here, we demonstrate that HSV-1 infection of iDCs and mDCs induces autophagy, which promotes the degradation of lamin A/C, B1, and B2 in iDCs only. This in turn facilitates the nuclear egress of progeny viral capsids and thus the formation of new infectious particles. In contrast, lamin protein levels remain stable in HSV-1-infected mDCs due to an inefficient autophagic flux. Elevated protein levels of KIF1B and KIF2A in mDCs inhibited lamin degradation, likely by hampering autophagosome-lysosome fusion. Therefore, in mDCs, fewer progeny capsids were released from the nuclei into the cytosol, and fewer infectious virions were assembled. We hypothesize that inhibition of autophagic lamin degradation in mDCs represents a very powerful cellular counterstrike to inhibit the production of progeny virus and thus viral spread.
CRIS-Team WoS Importer:2019-02-21

Autophagy-Mediated Breakdown of the nuclear lamina facilitates nuclear egress of HSV-1 capsids and thus generation of progeny virus in dendritic cells - Turan, A.; Krawczyk, A.; Grosche, Linda; Mühl-Zürbes, Petra; Drassner, C.; Hasenberg, M.; Voortmann, S.; Jastrow, H.; Kraner, Max; Doehner, K.; Sodeik, B.; Heilingloh, Christiane; et al. (2018)
EVALuna2:36213

CD83 and GRASP55 interact in human dendritic cells - Stein, Marcello F.; Blume, Katja; Heilingloh, Christiane; Kummer, Mirko; Biesinger, Brigitte; Sticht, Heinrich; Steinkasserer, Alexander (Biochemical and Biophysical Research Communications, 2015)
CD83 is one of the best known surface markers for mature human dendritic cells (DCs). The full-length 45 kDa type-I membrane-bound form (mbCD83) is strongly glycosylated upon DCs maturation. As co-stimulatory properties of CD83 are attributed to mbCD83 surface expression is required for efficient T-cell stimulation by mature DCs. By yeast two-hybrid screening, we were able to identify GRASP55 as interaction partner of CD83. DCs maturation induces endogenous CD83 protein expression with simultaneous regulation of CD83 glycosylation, interaction and co-localization with GRASP55 and CD83 surface exposure. GRASP55 is especially known for its role in maintaining Golgi architecture, but also plays a role in Golgi transport of specific cargo proteins bearing a C-terminal valine residue. Here we additionally demonstrate that binding of CD83 and GRASP55 rely on the C-terminal TELV-motif of CD83. Mutation of this TELV-motif not only disrupted binding to GRASP55, but also altered the glycosylation pattern of CD83 and reduced its membrane expression. Here we show for the first time that GRASP55 interacts with CD83 shortly after induction of DC maturation and that this interaction plays a role in CD83 glycosylation as well as in surface expression of CD83 on DCs.
EVALuna2:8259

Corrigendum to "Antibody-based immunotherapy of acyclovir resistant ocular herpes simplex virus infection" [Virology 512 (2017) 194-200] - Bauer, Dirk; Keller, Jessica; Alt, Mira; Schubert, Axel; Aufderhorst, Ulrich Wilhelm; Palapys, Vivien; Kasper, Maren; Heilingloh, Christiane; Dittmer, Ulf; Laffer, Bjoern; Eis-Huebinger, Anna Maria; Verjans, Georges M.; et al. (Virology, 2019)
EVALuna2:36334

Crystal Structure of the Extracellular Domain of the Human Dendritic Cell Surface Marker CD83 - Heilingloh, Christiane; Klingl, Stefan; Egerer-Sieber, Claudia; Schmid, Benedikt; Weiler, Sigrid; Mühl-Zürbes, Petra; Hofmann, Jörg; Stump, Joachim; Sticht, Heinrich; Kummer, Mirko; Steinkasserer, Alexander; Muller, Yves (Journal of Molecular Biology, 2017)
Keywords: homotypic interactions; immune co-stimulation and -suppression; structure–function relationships; V-set Ig-domain; X-ray crystallography

Herpes simplex virus type 1 ICP0 induces CD83 degradation in mature dendritic cells independent of its E3 ubiquitin ligase function - Heilingloh, Christiane; Muehl-Zuerbes, Petra; Steinkasserer, Alexander; Kummer, Mirko (Journal of General Virology, 2014)
Mature dendritic cells (mDCs) are the most potent antigen-presenting cells known today, as they are the only antigen-presenting cells able to induce naïve T-cells. Therefore, they play a crucial role during the induction of effective antiviral immune responses. Interestingly, the surface molecule CD83 expressed on mDCs is targeted by several viruses. As CD83 has been shown to exert co-stimulatory functions on mDCs, its downmodulation represents a viral immune escape mechanism. Mechanistically, it has been shown that herpes simplex virus type 1 infection leads to proteasomal degradation of CD83, resulting in a strongly diminished T-cell stimulatory capacity of the infected mDC. Previous data suggest that the viral immediate-early protein ICP0 (infected-cell protein 0) plays an important role in this process. In the present study, we showed that ICP0 is sufficient to induce CD83 degradation in the absence of any other viral factor. However, the mechanism of ICP0-mediated CD83 degradation is not yet understood. Here, we provide evidence that ubiquitination of lysine residues is, despite the published E3 ubiquitin ligase activity of ICP0, not necessary for CD83 degradation. This finding was underlined by the observation that expression of an ICP0 mutant lacking the E3 ubiquitin ligase domain in mDCs still induced CD83 degradation. Finally, inhibition of E1 activating enzyme using the specific inhibitor 4[4-(5-nitro-furan-2-ylmethylene)-3.5-dioxo-pyrazolidin-1-yl]-benzoic acid ethyl ester did not prevent CD83 degradation. Taken together, our data provide strong evidence that ICP0 alone induces CD83 degradation independent of its E3 ubiquitin ligase function and of the ubiquitin machinery.
EVALuna2:26033

Herpes simplex virus type-2 paralyzes the function of monocyte-derived dendritic cells - Grosche, Linda; Mühl-Zürbes, Petra; Ciblis, Barbara; Krawczyk, Adalbert; Kuhnt, Christine; Kamm, Lisa; Steinkasserer, Alexander; Heilingloh, Christiane (Viruses, 2020)
Herpes simplex viruses not only infect a variety of different cell types, including dendritic cells (DCs), but also modulate important cellular functions in benefit of the virus. Given the relevance of directed immune cell migration during the initiation of potent antiviral immune responses, interference with DC migration constitutes a sophisticated strategy to hamper antiviral immunity. Notably, recent reports revealed that HSV-1 significantly inhibits DC migration in vitro. Thus, we aimed to investigate whether HSV-2 also modulates distinct hallmarks of DC biology. Here, we demonstrate that HSV-2 negatively interferes with chemokine-dependent in vitro migration capacity of mature DCs (mDCs). Interestingly, rather than mediating the reduction of the cognate chemokine receptor expression early during infection, HSV-2 rapidly induces β2 integrin (LFA-1)-mediated mDC adhesion and thereby blocks mDC migration. Mechanistically, HSV-2 triggers the proteasomal degradation of the negative regulator of β2 integrin activity, CYTIP, which causes the constitutive activation of LFA-1 and thus mDC adhesion. In conclusion, our data extend and strengthen recent findings reporting the reduction of mDC migration in the context of a herpesviral infection. We thus hypothesize that hampering antigen delivery to secondary lymphoid organs by inhibition of mDC migration is an evolutionary conserved strategy among distinct members of Herpesviridae.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Adhesion; CYTIP; Cytohesin-1; Dendritic cells; HSV-1; HSV-2; LFA-1; Migration

HSV-1 Modulates IL-6 Receptor Expression on Human Dendritic Cells - Birzer, Alexandra; Krawczyk, Adalbert; Draßner, Christina; Kuhnt, Christine; Mühl-Zürbes, Petra; Heilingloh, Christiane; Steinkasserer, Alexander; Popella, Linda (Frontiers in Immunology, 2020)
Dendritic cells (DCs) are the guardians of the immune system since they are located in the majority of peripheral tissues. In addition, they are crucial for the induction of an effective immune response based on their unique capacity to stimulate naive T cells. During co-evolution, the human pathogen herpes simplex virus type 1 (HSV-1) has evolved several immune evasion mechanisms in order to subvert the host's immune system especially by targeting DC biology and function. Here we demonstrate that HSV-1 infection influences the IL-6 receptor (IL6R) expression both on protein and mRNA levels in/on human monocyte-derived mature DCs (mDCs). Surprisingly, reduced IL6R expression levels were also observed on uninfected bystander mDCs. Mechanistically, we clearly show that HSV-1-derived non-infectious light (L-) particles are sufficient to trigger IL6R regulation on uninfected bystander mDCs. These L-particles lack the viral DNA-loaded capsid and are predominantly produced during infection of mDCs. Our results show that the deletion of the HSV-1 tegument protein vhs partially rescued the reduced IL6R surface expression levels on/in bystander mDCs. Using a neutralizing antibody, which perturbs the transfer of L-particles to bystander mDCs, was sufficient to rescue the modulation of IL6R surface expression on uninfected bystander mDCs. This study provides evidence that L-particles transfer specific viral proteins to uninfected bystander mDCs, thereby negatively interfering with their IL6R expression levels, however, to a lesser extend compared to H-particles. Due to their immune-modulatory capacity, L-particles represent an elaborated approach of HSV-1-mediated immune evasion.
CRIS-Team Scopus Importer:2020-09-18
Keywords: bystander cells; HSV-1; IL-6 receptor; L-particles; mature dendritic cells; vhs

Human Cytomegalovirus-Induced Degradation of CYTIP Modulates Dendritic Cell Adhesion and Migration - Grosche, Linda; Drassner, Christina; Mühl-Zürbes, Petra; Kamm, Lisa; Vu Thuy Khanh Le-Trilling; Trilling, Mirko; Steinkasserer, Alexander; Heilingloh, Christiane (Frontiers in Immunology, 2017)
As potent antigen-presenting cells, dendritic cells (DCs) are essential for the initiation of effective antiviral immune responses. Viruses and especially herpesviruses, which are able to establish lifelong persistence, exploit several immune evasion mechanisms targeting DC biology. Our group has previously shown that the ?-herpesvirus herpes simplex virus type 1 inhibits mature DC (mDC) migration by inducing adhesion via degrading the cellular protein CYTIP (cytohesin-1 interacting protein), an important negative regulator of ?2-integrin activity. In the present study, we extended our analysis to the ?-herpesvirus human cytomegalovirus (HCMV), to investigate whether other herpesviridae also induce such modulations. Indeed, HCMV impairs mDC transwell migration capability following a CCL19-chemokine gradient, despite equivalent expression levels of the cognate chemokine receptor CCR7 at the corresponding time points post-infection. Remarkably, HCMV infection potently induced ?2-integrin activity on mDCs. Furthermore, directly HCMV-infected mDCs, exhibiting viral gene expression, strongly adhere to fibronectin and ICAM-1, in contrast to mDCs lacking infection or viral gene expression. Interestingly, HCMV-positive mDCs display a proteasome-dependent degradation of CYTIP. Contrasting the migration toward CCL19, elevated expression levels of the chemokine receptor CXCR4 in HCMV-infected mDCs were associated with functional CXCL12-chemotaxis under the herein used conditions. In summary, our results show that HCMV shapes mDC adhesion to compromise migration toward CCL19, but retaining CXCL12 responsiveness. Thus, we hypothesize that a preferred migration pattern toward the bone marrow, but not to secondary lymphoid organs, could ultimately cause a failure in the induction of potent antiviral immune responses.
EVALuna2:26038

Human cytomegalovirus interferes with dendritic cell adhesion and migration via the proteasomal degradation of the cytohesin-1 interacting protein - Grosche, Linda; Drassner, C.; Mühl-Zürbes, Petra; Kamm, L.; Le-Trilling, V. T. K.; Trilling, M.; Steinkasserer, Alexander; Heilingloh, Christiane (2018)
EVALuna2:36215

L Particles Transmit Viral Proteins from Herpes Simplex Virus 1-Infected Mature Dendritic Cells to Uninfected Bystander Cells, Inducing CD83 Downmodulation - Heilingloh, Christiane; Kummer, Mirko; Muehl-Zuerbes, Petra; Drassner, Christina; Daniel, Christoph; Klewer, Monika; Steinkasserer, Alexander (Journal of Virology, 2015)
Mature dendritic cells (mDCs) are known as the most potent antigen-presenting cells (APCs) since they are also able to prime/induce naive T cells. Thus, mDCs play a pivotal role during the induction of antiviral immune responses. Remarkably, the cell surface molecule CD83, which was shown to have costimulatory properties, is targeted by herpes simplex virus 1 (HSV-1) for viral immune escape. Infection of mDCs with HSV-1 results in downmodulation of CD83, resulting in reduced T cell stimulation. In this study, we report that not only infected mDCs but also uninfected bystander cells in an infected culture show a significant CD83 reduction. We demonstrate that this effect is independent of phagocytosis and transmissible from infected to uninfected mDCs. The presence of specific viral proteins found in these uninfected bystander cells led to the hypothesis that viral proteins are transferred from infected to uninfected cells via L particles. These L particles are generated during lytic replication in parallel with full virions, called H particles. L particles contain viral proteins but lack the viral capsid and DNA. Therefore, these particles are not infectious but are able to transfer several viral proteins. Incubation of mDCs with L particles indeed reduced CD83 expression on uninfected bystander DCs, providing for the first time evidence that functional viral proteins are transmitted via L particles from infected mDCs to uninfected bystander cells, thereby inducing CD83 downmodulation.HSV-1 has evolved a number of strategies to evade the host's immune system. Among others, HSV-1 infection of mDCs results in an inhibited T cell activation caused by degradation of CD83. Interestingly, CD83 is lost not only from HSV-1-infected mDCs but also from uninfected bystander cells. The release of so-called L particles, which contain several viral proteins but lack capsid and DNA, during infection is a common phenomenon observed among several viruses, such as human cytomegalovirus (HCMV), Epstein-Barr virus, and HSV-1. However, the detailed function of these particles is poorly understood. Here, we provide for the first time evidence that functional viral proteins can be transferred to uninfected bystander mDCs via L particles, revealing important biological functions of these particles during lytic replication. Therefore, the transfer of viral proteins by L particles to modulate uninfected bystander cells may represent an additional strategy for viral immune escape.
EVALuna2:19522

PGAM5-MAVS interaction regulates TBK1/ IRF3 dependent antiviral responses - Yu, Yidong; Zielinska, Marta; Li, Wei; Bernkopf, Dominic; Heilingloh, Christiane; Neurath, Markus; Becker, Christoph (Scientific Reports, 2020)
Viral infections trigger host innate immune responses, characterized by the production of type-I interferons (IFN) including IFNβ. IFNβ induces cellular antiviral defense mechanisms and thereby contributes to pathogen clearance. Accumulating evidence suggests that mitochondria constitute a crucial platform for the induction of antiviral immunity. Here we demonstrate that the mitochondrial protein phosphoglycerate mutase family member 5 (PGAM5) is important for the antiviral cellular response. Following challenge of HeLa cells with the dsRNA-analog poly(I:C), PGAM5 oligomers and high levels of PGAM5 were found in mitochondrial aggregates. Using immunoprecipitation, a direct interaction of PGAM5 with the mitochondrial antiviral-signaling protein (MAVS) was demonstrated. In addition, PGAM5 deficient cells showed diminished expression of IFNβ and IFNβ target genes as compared to WT cells. Moreover, PGAM5 deficient mouse embryonic fibroblasts (MEFs) exhibited decreased phosphorylation levels of IRF3 and TBK1 when challenged with poly(I:C) intracellularly. Finally, PGAM5 deficient MEFs, upon infection with vesicular stomatitis virus (VSV), revealed diminished IFNβ expression and increased VSV replication. Collectively, our study highlights PGAM5 as an important regulator for IFNβ production mediated via the TBK1/IRF3 signaling pathway in response to viral infection.
CRIS-Team Scopus Importer:2020-06-02

Role of L-Particles during Herpes Simplex Virus Infection - Heilingloh, Christiane; Krawczyk, Adalbert (Frontiers in Microbiology, 2017)
Infection of eukaryotic cells with α-herpesviruses results in the formation and secretion of infectious heavy particles (virions; H-particles) and non-infectious light particles (L-particles). Herpes simplex virus type 1 (HSV-1) H-particles consist of a genome-containing capsid surrounded by tegument proteins and a glycoprotein-rich lipid bilayer. Non-infectious L-particles are composed mainly of envelope and tegument proteins and are devoid of capsids and viral DNA. L-particles were first described in the early nineties and from then on investigated for their formation and role during virus infection. The development and secretion of L-particles occur simultaneously to the assembly of complete viral particles. HSV-1 L-particles are assembled by budding of condensed tegument into Golgi-delivered vesicles and are capable of delivering their functional content to non-infected cells. Thereby, HSV-1 L-particles contribute to viral pathogenesis within the infected host by enhancing virion infectivity and providing immune evasion functions. In this review we discuss the emergence of HSV-1 L-particles during virus replication and their biological functions described thus far.
EVALuna2:35398

siRNA Electroporation to Modulate Autophagy in Herpes Simplex Virus Type 1-Infected Monocyte-Derived Dendritic Cells - Düthorn, Alexandra; Turan, Aykut; Drassner, Christina; Muehl-Zurbes, Petra; Heilingloh, Christiane; Steinkasserer, Alexander; Grosche, Linda (Journal of Visualized Experiments, 2019)
Herpes simplex virus type-1 (HSV-1) induces autophagy in both, immature dendritic cells (iDCs) as well as mature dendritic cells (mDCs), whereas autophagic flux is only observed in iDCs. To gain mechanistic insights, we developed efficient strategies to interfere with HSV-1-induced autophagic turnover. An inhibitor-based strategy, to modulate HSV-1-induced autophagy, constitutes the first choice, since it is an easy and fast method. To circumvent potential unspecific off-target effects of such compounds, we developed an alternative siRNA-based strategy, to modulate autophagic turnover in iDCs upon HSV-1 infection. Indeed, electroporation of iDCs with FIP200-specific siRNA prior to HSV-1 infection is a very specific and successful method to ablate FIP200 protein expression and thereby to inhibit autophagic flux. Both presented methods result in the efficient inhibition of HSV-1-induced autophagic turnover in iDCs, whereby the siRNA-based technique is more target specific. An additional siRNA-based approach was developed to selectively silence the protein expression of KIF1 B and KIF2A, facilitating autophagic turnover upon HSV-1 infection in mDCs. In conclusion, the technique of siRNA electroporation represents a promising strategy, to selectively ablate the expression of distinct proteins and to analyze their influence upon an HSV-1 infection.
CRIS-Team WoS Importer:2019-11-15

The Major Immediate-Early Protein IE2 of Human Cytomegalovirus Is Sufficient to Induce Proteasomal Degradation of CD83 on Mature Dendritic Cells - Heilingloh, Christiane; Grosche, Linda; Kummer, Mirko; Mühl-Zürbes, Petra; Kamm, Lisa; Scherer, Myriam; Latzko, Melanie; Stamminger, Thomas; Steinkasserer, Alexander (Frontiers in Microbiology, 2017)
Human cytomegalovirus (HCMV) is the prototypic beta-herpesvirus and widespread throughout the human population. While infection is asymptomatic in healthy individuals, it can lead to high morbidity and mortality in immunocompromised persons. Importantly, HCMV evolved multiple strategies to interfere with immune cell function in order to establish latency in infected individuals. As mature DCs (mDCs) are antigen-presenting cells able to activate naïve T cells they play a crucial role during induction of effective antiviral immune responses. Interestingly, earlier studies demonstrated that the functionally important mDC surface molecule CD83 is down-regulated upon HCMV infection resulting in a reduced T cell stimulatory capacity of the infected cells. However, the viral effector protein and the precise mechanism of HCMV-mediated CD83 reduction remain to be discovered. Using flow cytometric analyses, we observed significant down-modulation of CD83 surface expression becoming significant already 12 h after HCMV infection. Moreover, Western bot analyses revealed that, in sharp contrast to previous studies, loss of CD83 is not restricted to the membrane-bound molecule, but also occurs intracellularly. Furthermore, inhibition of the proteasome almost completely restored CD83 surface expression during HCMV infection. Results of infection kinetics and cycloheximide-actinomycin D-chase experiments, strongly suggested that an HCMV immediate early gene product is responsible for the induction of CD83 down-modulation. Consequently, we were able to identify the major immediate early protein IE2 as the viral effector protein that induces proteasomal CD83 degradation.
EVALuna2:26039